Evaluation of Human Resource Planning Effectiveness in Reducing Fraud and Enhancing Employee Professionalism at Cireng Borojol MSMEs - Laraswati Laraswati; Aghnia Syahrunnisa; TB. Hamim Riski; Resya Dwi Marselinna (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Workforce planning plays an essential role in supporting effective human resource management, particularly in Micro, Small, and Medium Enterprises (MSMEs) experiencing business growth. This study aims to evaluate the effectiveness of human resource planning in reducing fraud and enhancing employee professionalism at Cireng Borojol MSMEs. A descriptive qualitative method was employed through direct interviews with the business owner. The findings show that Cireng Borojol, established in 2021, has developed from a simple food business into an MSME utilizing resellers, social media, and online marketplaces for marketing expansion. The company currently employs approximately 40 workers distributed across several operational divisions. Key challenges include employee unprofessional behavior, job placement mismatches, work fatigue, and financial reporting inconsistencies that may indicate potential fraud risks. To address these issues, the company applies periodic performance evaluations, prioritizes employee comfort, and implements a reward system based on performance achievement. The results indicate that human resource planning supported by evaluation and reward mechanisms contributes to improving employee professionalism and reducing potential fraud in operational activities.